2007
DOI: 10.1002/art.22439
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of stromal cell–derived factor 1 (CXCL12) production in rheumatoid synovial fibroblasts through interactions with T lymphocytes: Role of interleukin‐17 and CD40L–CD40 interaction

Abstract: Objective. Stromal cell-derived factor 1 (SDF-1) is a potent chemoattractant for memory T cells in inflamed rheumatoid arthritis (RA) synovium. This study was undertaken to investigate the effect of interleukin-17 (IL-17) and CD40-CD40L interaction on SDF-1 production in RA fibroblast-like synoviocytes (FLS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 40 publications
3
95
0
Order By: Relevance
“…However, the current knowledge on how SDF-1 may be regulated, especially in tumors, is very limited. It is reported that IL-17 induces the production of SDF-1, as well as the expression of SDF-1 mRNA, in cultured Rheumatoid synovial fibroblasts in a dose-dependent manner (32). Interestingly, in a murine bone stromal cell line, SDF-1 expression is found to be down-regulated by TGFh-1, both at the mRNA level and at the protein level (33).…”
Section: Discussionmentioning
confidence: 98%
“…However, the current knowledge on how SDF-1 may be regulated, especially in tumors, is very limited. It is reported that IL-17 induces the production of SDF-1, as well as the expression of SDF-1 mRNA, in cultured Rheumatoid synovial fibroblasts in a dose-dependent manner (32). Interestingly, in a murine bone stromal cell line, SDF-1 expression is found to be down-regulated by TGFh-1, both at the mRNA level and at the protein level (33).…”
Section: Discussionmentioning
confidence: 98%
“…CXCR4 is reported to be the predominant mechanism for the recruitment of circulating fibrocytes to the lungs (18), and CXCR4 has been shown to be critical for mesenchymal stem cell recruitment to bone in mice (19). The CXCR4 ligand stromal cell-derived factor 1 (CCL12) is up-regulated in both RA serum and synovial tissue (20). Additionally, antagonism of CXCR4 reduces inflammation in CIA (21).…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines also play a key role in the accumulation of inflammatory cells. 34 Their aberrant expression may be responsible for the induction of chronic inflammatory processes such as rheumatoid arthritis (RA), 35 multiple sclerosis (MS), 36 colitis ulcerosa (CU) 37 and allergic diseases. 38 SDF-1 may be a common downstream executor of inflammatory cell accumulation regardless of circumstances upregulating its expression.…”
Section: Cell-based Therapymentioning
confidence: 99%